Preliminary Reflections to Think Training of Trainers in the Modern University: New Look and New Dialogs from the Perspective of Complexity - Jorge Alberto Ferrada-Sullivan (Revista Electronic@ Educare, 2017)
This article reflects on the epistemological principles underlying Morin’s complex thought in their relation with the formative and pedagogical processes in Chilean classrooms. The paper theme aims to relate the direct connection between the fundamental notions of the concept of complexity and the evaluation of certain active methodological principles enhancing the reflexivity and the students’ experience. The three basal and pedagogical assumptions of such connection are based on relations of dialog with the contextual diversity in the recursivity of the experience and in the hologramatic principle of knowledge. The purpose of the text is based on the presentation of critical arguments that allow tensioning the traditional ways of teaching and learning within the educational spaces. Conceptually, the notion of complexity allows the discussion with the educational tradition and with elements of change for a practical reflexivity on formative processes. These processes carry and imply new cognitive landscapes about teaching. The learning experience, the creative autonomy and the current context will be key foundations for future systemic transformations. Finally, a set of recommendations are proposed to implement active methodological actions that could be used in the various educational spaces in Chile.